Open border ecosystems: Against globalised laissez-faire conservation - Christopher H Lean (Cambridge Prisms: Extinction)
Ecosystems are increasingly being represented as marketplaces that produce goods for humanity, and because of this, economic metaphors for increasing efficiency have been introduced into conservation. A powerful model for economic growth is the globalised free market, and some are implicitly deploying it to suggest changes in conservation practice. Ecological globalisation is the position that we should not control the free movement of species and rewilding occurs most efficiently through non-intervention. When species can move and interact with new ecological systems, they create novel ecosystems. These novel arrangements create experimental markets in nature’s economy, providing opportunities for the efficient production of goods for humans, also known as ecosystem services. When invasive species supersede local populations, it indicates previous biotic systems were inefficient, which is why they were replaced, and therefore, it is wrong to protect indigenous “losers” from extinction. Those who defend indigenous species are accused of being xenophobic against recent biotic migrants. This position is flawed both empirically and morally as there is a disconnect between these economic and political arguments when applied to human economies and nature’s economy.